Institutional Quality Management Based on Strengthening Accreditation of Study Programs at Islamic State University of North Sumatera - Khairuddin Khairuddin; Yusuf Hadijaya (Edumaspul: Jurnal Pendidikan, 2023)
In general, Islamic Religious Higher Education Institutions in Indonesia obtain Accreditation status of Higher Education Institutions which are still B and the accumulation of all Study Program Accreditation statuses that have achieved A is still less than 50%. The Accreditation Rating for Study Programs and Institution Accreditation is a result that cannot be changed directly, meaning that these changes can only be achieved through the processes and stages in the Quality Management System. The level of customer satisfaction with the quality of service provided by educational institutions to customers, namely on the other hand, if the process goes well, it will not be enough to produce good service, because a good service also depends on good input. That input then becomes a requirement whether a good process can be carried out to produce a good service. Based on this assumption, a quality management system was born, institutions need to clearly define the provision and service standards they will provide. Improving the quality of education is carried out through implementing a Quality Management System for; (1) carrying out an accountable higher education system through efforts to achieve its vision, (2) carrying out best practices in carrying out daily work, and (3) efforts to always carry out sustainable development so that it is always in accordance with the demands of the times and evolving needs and expectations in society.